EVALUASI PELAKSANAAN PROGRAM BIMBINGAN DAN KONSELING BIDANG PRIBADI DI SMPN 3 KRAGILAN - Tsulistia Poetry Hendrawan; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
BK teachers have an important role in developing guidance and counseling programs for students. Based on the results of the need assessment of SMPN 3 Kragilan students, it shows that the main problems occur in the personal sector, so the purpose of this study is to find out how the success of the counseling program is designed in accordance with the need assessment, evaluation and follow-up of the counseling program that has been implemented, as well as obstacles in implementation of the BK program in schools. The method used in this study is a naturalistic qualitative approach, data collection is done through observation, interviews and documentation.